Healthcare Providers’ Perceptions of Vulnerability to Domestic Sex Trafficking in Ontario: A Qualitative Study - Corinne Rogers; Soumyaa Veerakumar Subramanium; Rhonelle Bruder; Robin Mason; Janice Du Mont (Health Services Insights)
Background: Domestic sex trafficking is a prevalent health and human rights issue in Ontario, Canada. Although providers working in healthcare settings are uniquely positioned to identify and care for individuals who are sex trafficked, they may be hampered by a limited understanding of who is vulnerable to being sex trafficked and, thereby, fail to recognize those in need of support. Objectives: This qualitative study, part of a larger program of research, sought to apply critical social theory, and intersectionality to explore providers’ perceptions of who is vulnerable to domestic sex trafficking. Methods: Thirty-one healthcare providers of diverse identities and professional backgrounds were interviewed, using open-ended semi-structured questions, between November 2022 and February 2023. The interviews were analyzed using Braun and Clarke’s reflexive thematic analysis framework and organized by a modified Taxonomy of Vulnerability. Results: Three themes were generated: Traumatic history, social identities and relationships, and structural determinants. Providers consistently identified being female as a vulnerability to domestic sex trafficking. Few providers referenced the intersections of being female with other sociodemographic characteristics or acknowledged the complex ways in which larger systems have perpetuated the marginalization and inequitable status of some persons. Conclusion: The findings emphasize the urgent need to understand vulnerability as more than just an individual condition. Further, provider training must cultivate critical consciousness to recognize the contextual roots of vulnerability and how the role and socialization processes of larger systems in perpetuating vulnerabilities differently across individuals’ lives.